72 residues of gal repressor fused to beta-galactosidase repress the gal operon of E. coli. - von Wilcken-Bergmann, B (1983)
An active gene has been constructed which produces a chimera consisting of the N-terminal domain of the gal repressor and all but the first five residues of beta-galactosidase. Seventy two residues of gal repressor fused to beta-galactosidase as tetrameric core are sufficient to repress the gal operon in vivo and to bind to the gal operator in vitro.